Use of graphic design software in linear business processors (Journal of the College of Basic Education, 2023)
The idea of the design work depends on whatever its treatments are, whether in the intellectual orJob given and at all stages of completion on a set of foundations and methodsStructural elements that process text, digital graphic processing, depend on a set ofSoftware and digital processing tools, which positively affected the employment of thoseTreatments to clarify the visual semantic and aesthetic dimension consistent with the design ideaIn addition to that, the enhancements granted by these processors to enrich the linear visual achievementThe processor digitizes the new readability or gives the text a new mosaic for multiple readings and notOne closed reading, according to the expression of (Julia Kristeva), who cared about the multi-reading of the textMosaic and considered it a mosaic of all colors. And the current research took upon itself the task of researchInvestigating aspects of that; By organizing it according to four chapters; includedThe first chapter includes the research problem that the researcher touched, and it is related to the field of linear painting treatmentin digital designs; He asked the following question as a problem for his research: What are the design treatments?Using digital graphics programs in written works?The importance of the research was determined by:Developing conceptual awareness among workers in the field of digital graphic design.What the digital software contributes to a new conceptual development for reading the written achievement on theThe aesthetic and functional level, and giving linear achievements space for cross-fertilization and communication withModern and contemporary global achievements.The search was determined by the following